To neutrally offer or strongly recommend? General practitioners' perspectives on screening for gestational diabetes according to the national guideline in Norway - Ingeborg Forthun; Kathy Ainul Møen; Stefán Hjörleifsson (Taylor & Francis Group, 2024)
Objective To explore general practitioners' experiences and reflections on how the current Norwegian guideline for screening for gestational diabetes affects their clinical practice.Design A qualitive study in which data were collected through semi-structured focus group interviews and analyzed thematically.Setting and subjects Five focus groups conducted in 2020 among GPs in Norway; three interviews took place face-to-face and two were held digitally. The total number of participants was 31.Results GPs acknowledged the potential benefits of more extensive screening, but had concerns about the medicalization of pregnancy, stating that some women experienced considerable anxiety. The GPs expressed doubts about the guideline's evidence base but differed in how they interpreted what the guideline was asking them to do. Some offered eligible women the opportunity to be screened, while other set up a screening appointment without consulting the women first. For some, fear of incrimination made them recommend screening without being convinced that it was the right thing for the patient.Conclusions It is unclear whether the guideline for gestational diabetes requires GPs to recommend screening to pregnant women or if they should provide neutral information about the availability of screening. This ambiguity should be addressed, and the guideline evaluated against the core principles of general practice.